Malaria Infection and Socioeconomics in Malaria Endemic Areas of East Nusa Tenggara, Indonesia - Nisa Fauziah; Edina Anindhita; Savira Ekawardhani; Deviyanthi Nur Afifah; Jontari Hutagalung (Majalah Kedokteran Bandung, 2023)
More than 1.1 million people, or 20.90% of the population in East Nusa Tenggara (NTT), Indonesia, live below the poverty line, making NTT the third province with the highest number of poor people in Indonesia. The region of NTT, which is well known as one of the endemic areas for malaria in Indonesia, also has the highest number of adults with low nutritional status. This study aimed to assess the influence of socioeconomic factors on malaria-endemic areas in eastern Indonesia. A cross-sectional study was conducted in East Nusa Tenggara from January to March 2020. Bivariate and multivariate analyses were then performed on 317 population data of adults with low socioeconomic status. It was found that one of the socioeconomic factors, i.e., the age, is significantly associated with malaria (p-value = 0.031; OR = 1.684) with 40 being the age with the highest association. Thus, age is associated with malaria incidence in endemic areas.